Nyāyavārttikam = Nyāya-vārttikam : a gloss on Vātsyāyaṇa's commentary of the Nyāya-aphorisms - Uddyotakara (Eastern Book Linkers, 1986)
Gloss on a classical work on Nyāya philosophy; includes Nyāyasūtra of Gautama.